Células tronco mesenquimais: diferenciação osteogênica in vitro estimulada pela atividade física in vivo com e sem bloqueio de óxido nitrico sintase e sua aplicação no tratamento local de osteoporose de ratas - Natalia de Melo Ocarino (2008)
Three experiments were performed. The experiment 1 evaluated the effect of the physicalactivity with and without the nitric oxide synthase inhibition in the bone histomorfometry of ratswith osteoporosis. The experiment 2 evaluated the osteogenic differentiation in vitro ofmesenchymal stem cells (MSCs) of rats with osteoporosis submitted to the physical activitywith and without nitric oxide synthase inhibition. The experiment 3 evaluated the effect of theintra-bone injection of differentiated MSCs in vitro in the treatment of the femoral osteoporosisof rats. It was conclude that the nitric oxide acts as mediator of the effects of the physicalactivity on the bone of rats with osteoporosis. MSCs of the rats with osteoporosis presentedsmaller osteogenic differentiation. The physical activity increased the osteogenic differentiationof MSCs of rats with osteoporosis. The nitric oxide synthase inhibition had negative effect inthe osteogenic differentiation of MSCs of normal rats and with osteoporosis submitted to thephysical activity, but it increased the osteogenic differentiation of MSCs of rats with sedentaryosteoporosis. The treatment of the femoral osteoporosis with differentiated MSCs promotedincrease the trabecular bone percentage for values similar to the control group in the wholefemur